Radon/thoron and progeny levels in dwellings: Regional variations and effect of dwelling characteristics – A case study in Jalandhar district of Punjab, India. Issue 5 (June 2018) - Kumar, Manish; Kaushal, Anjali; Sarin, Amit; Kumar, Rajesh; Sharma, Navjeet
An extensive survey to measure natural radioactivity in human environment in Jalandhar district of Punjab was undertaken. Results of measurements of indoor radon/thoron and their progeny concentrations are being presented here. Single-entry, pin-hole dosemeters were used for the measurement of radon/thoron concentrations. Deposition-based direct radon/thoron progeny sensors were used for measurement of progeny concentrations. The results have been analysed on the basis of regional characteristics, type of construction and building material used. The radon concentration was found to vary from 6.64 ± 1.72 Bq/m 3 to 47.18 ± 4.43 Bq/m 3 with geometric mean value of 17.9 ± 2.91 Bq/m 3 while the thoron concentration varies from 7.75 ± 2.54 Bq/m 3 to 82.68 ± 8.33 Bq/m 3 with geometric mean value of 33.54 ± 5.09 Bq/m 3 . The geometric mean value of equilibrium factor for indoor radon and thoron was found to be 0.43 and 0.02, respectively. The estimated annual inhalation dose varies from 0.22 mSv to 1.76 mSv with geometric mean value of 0.66 mSv. Correlation of indoor radon and air gamma dose rate was also studied.